(±)-Evodiakine, A Pair of Rearranged Rutaecarpine-Type Alkaloids From Evodia rutaecarpa - Li, Yan-Hong (Nat Prod Bioprospect, 2016)
ABSTRACT: (±)-Evodiakine (1a and 1b), a pair of rearranged rutaecarpine-type alkaloids with an unprecedented 6/5/5/7/6 ring system, were isolated from the nearly ripe fruits of Evodia rutaecarpa. Separation of the enantiomers have been achieved by chiral HPLC column. The structures of (±)-evodiakine were unambiguously elucidated by 1D and 2D NMR spectra, mass spectrometry, and single-crystal X-ray diffraction. Their absolute configurations were determined by comparison of experimental and calculated electronic circular dichroism spectra. A hypothetical biogenetic pathway for (±)-evodiakine was also proposed. Compounds 1a, 1b, and the racemate (1) were tested for their cytotoxic and anti-inflammatory activities. GRAPHICAL ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13659-016-0113-7) contains supplementary material, which is available to authorized users.